The Influence Of Work Spirit And Training On Work Performance Of Employees Of Pt. Unikitz United Group Medan - Cindy (Enrichment : Journal of Management, 2022)
PT. Unikitz Bersatu Group is: a private company that has just been established since 2016 having its address at Jalan Williem Iskandar Komp. MMTC Block K No. 3, Medan. The research population that will be used in the study are all employees who work at the company as many as 48 employees. In relation to the total population is: 48 employees, then the determination of the sample using saturated sampling. Simultaneously there is a significant influence between the variables of work spirit and training on employee turnover of PT. Unikitz United Group. While partially found the variable morale has a significant effect on employee turnover of PT. Unikitz United Group. Partially, it was found that the training variable had a significant effect on employee turnover at PT. Unikitz United Group. The results of this study indicate that the training variable has more influence than morale on employee turnover at PT. Unikitz United Group